Nationwide survey on current management strategies of toddler's fractures. Issue 5 (26th July 2017) - Seguin, Jade; Brody, Daniel; Li, Patricia
ABSTRACT: Background: Tibial fractures are common in children less than 3 years old. The traditional management involves immobilization in an above knee cast for both confirmed (positive x-ray) and presumed (normal x-ray) toddler's fractures. This carries health care implications and causes unnecessary burden for patients and their families. There is a paucity of literature describing the ideal immobilization strategy for this injury. Objectives: To determine: 1) the variation between Canadian emergency departments in management of toddler's fractures; 2) the variation in management between confirmed and presumed toddler's fractures; 3) the association between demographic variables and immobilization strategies. Methods: This was an email survey of all members of the Pediatric Emergency Research Canada network. The survey consisted of 2 clinical vignettes followed by multiple-choice questions. Results: Survey response rate was 73% (153/211). For confirmed toddler's fractures, 39% of physicians chose to immobilize with above knee circumferential cast, 27% with below knee circumferential cast and 20% with below knee splint. For presumed toddler's fractures, 44% of respondents chose to manage without casting, 22% with below knee splint and 14% with above knee circumferential cast. There was significant practice variation between Canadian pediatric emergency departments for both types of fractures and between the management of confirmed and presumed toddler's fractures. Conclusions: Our study is the first to identify nationwide variation in the management of toddler's fractures. This variation highlights the need for future research to compare the different management strategies to determine families' preferences and functional outcomes in children with these injuries. RÉSUMÉ: Contexte: Les fractures du tibia sont fréquentes chez les enfants de moins de 3 ans. La prise en charge habituelle consiste en l'immobilisation de la jambe par la pose d'un plâtre au-dessus du genou, et ce, tant pour les fractures avérées (cliché radiologique positif) que pour les fractures présumées (cliché radiologique normal), ce qui implique des soins de santé et impose un fardeau inutile aux patients et à leur famille. Toutefois, il existe peu de documentation sur le meilleur type d'immobilisation à choisir en pareil cas. Objectifs: L'étude visait à déterminer : 1) les différences de prise en charge des fractures des tout-petits entre les services des urgences au Canada; 2) les différences de prise en charge entre les fractures avérées et les fractures présumées; 3) les associations entre les variables démographiques et les types d'immobilisation. Méthode: Il s'agit d'une enquête menée parmi tous les membres du réseau Pediatric Emergency Research Canada, qui ont été informés par courriel. Le questionnaire consistait en deux scénarios cliniques, suivis de questions à choix multiple. Résultats: Le taux de réponse a atteint 73 % (153/211). Dans les cas de fracture avérée des tout-petits, 39 % des médecins ont choisi l'immobilisation du membre par la pose d'un plâtre circulaire au-dessus du genou et 27 %, par la pose d'un plâtre circulaire au-dessous du genou, tandis que 20 % ont choisi l'immobilisation du membre par la pose d'une attelle au-dessous du genou. Quant aux fractures présumées des tout-petits, 44 % des répondants ont choisi un traitement sans pose de plâtre; 22 %, un traitement avec pose d'une attelle au-dessous du genou, et 14 %, avec pose d'un plâtre circulaire au-dessus du genou. Des différences importantes de pratique ont été relevées entre les services des urgences pédiatriques au Canada en ce qui concerne les deux types de fracture, de même qu'entre la prise en charge des fractures avérées et des fractures présumées des tout-petits. Conclusion: L'étude en question est la première à cerner les différences de prise en charge des fractures des tout-petits à l'échelle du pays. Les résultats font ressortir la nécessité de comparer, dans de futures études, les différentes stratégies de prise en charge afin de déterminer le degré de satisfaction des familles et les résultats fonctionnels chez les enfants affectés.